2020
DOI: 10.22271/chemi.2020.v8.i4an.10152
|View full text |Cite
|
Sign up to set email alerts
|

Mean performance of growth, yield and quality parameters of parents and F1 hybrids of pooled data in brinjal (Solanum melongena L.) over coastal Andhra Pradesh conditions

Abstract: The present study was conducted to assess the general combining ability effects of parents and specific combining ability effects of hybrids for qualitative and quantitative traits and explore their use in hybrid development. Twenty one eggplant hybrids generated by 7 × 7 half diallel and evaluated along with their 7 parents and 2 checks. Seven elite parents viz., Pennada, EC-169084, Bhagyamati, Babajipet-1, Babajipet-2, EC-169089 and Tuni Local were crossed in half-diallel fashion and the resultant 21 hybrids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…The challenge of finding a hybrid with stability for all the traits, showing the scope for the inclusion of more environments for future analysis. Siva et al (2020) reached a similar type of result.…”
Section: Average Stable Genotypessupporting
confidence: 60%
“…The challenge of finding a hybrid with stability for all the traits, showing the scope for the inclusion of more environments for future analysis. Siva et al (2020) reached a similar type of result.…”
Section: Average Stable Genotypessupporting
confidence: 60%
“…(2016) [14] , Ramani et al (2017) [12] , Patil et al (2019) [8] and Siva et al (2020) [15] . In the present study, significant GCA effects were observed for majority of the traits.…”
Section: Resultsmentioning
confidence: 99%
“…The brinjal crop plays a pivotal role in attaining nutritional security through vegetables. The success of a breeding program hinges on the careful selection of parents and a comprehensive understanding of the genetic mechanisms influencing various traits (Siva et al, 2020). Breeders can optimize cross-combinations in hybridization by carefully selecting parent generations based on their general combining ability (GCA) and specific combining ability (SCA) (Vamsi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%